2020
DOI: 10.1002/app.50234
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive properties of promising energy storage material based on thiophene containing perylenediimide polymer

Abstract: In this study, electropolymerization of pre‐synthesized N,N′‐di‐[3‐[2‐(3‐thienyl)ethyl] phenyl] perylene‐3,4,9,10‐bis(dicarboximide) (ThPDITh) was performed on Au button electrode and the properties of the resultant polymer P(ThPDITh) were investigated by electrochemical techniques. Effect of the polymerization charge on the redox behaviors of the polymer film was investigated by cyclic voltammetry (CV) and the polymer film was further characterized by electrochemical impedance spectroscopy (EIS) measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The logarithmic relationship between I p and υ , which provides more detailed information about the energy‐storage systems, is given in Equation (1), [ 59 ] where the slope (b) is 1.0 for capacitive materials and 0.5 for battery‐type materials. Although a clear‐cut boundary is not easy to define, materials such as conductive polymers, having a “transition” area between capacitive and battery‐type behaviors, are defined as pseudocapacitive hybrid energy‐storage systems, falling into the range of 0.5–1.0 Vlog Ip= log a + b log υRegarding our system, b was found to be 0.99 (Figure 3d), indicating that the P[Th 3 CNTT–TPA] film had a pseudocapacitive hybrid polymer behavior, demonstrating capacitor and battery properties together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The logarithmic relationship between I p and υ , which provides more detailed information about the energy‐storage systems, is given in Equation (1), [ 59 ] where the slope (b) is 1.0 for capacitive materials and 0.5 for battery‐type materials. Although a clear‐cut boundary is not easy to define, materials such as conductive polymers, having a “transition” area between capacitive and battery‐type behaviors, are defined as pseudocapacitive hybrid energy‐storage systems, falling into the range of 0.5–1.0 Vlog Ip= log a + b log υRegarding our system, b was found to be 0.99 (Figure 3d), indicating that the P[Th 3 CNTT–TPA] film had a pseudocapacitive hybrid polymer behavior, demonstrating capacitor and battery properties together.…”
Section: Resultsmentioning
confidence: 99%
“…The regression value of the υ-I p graph was found to be higher than that of υ ½ ÀI p graph, indicating the rate controlling electrontransfer reaction of thin-film behavior of P[Th 3 CNTT-TPA] (Figure 3b,c). [52,57,58] The logarithmic relationship between I p and υ, which provides more detailed information about the energy-storage systems, is given in Equation ( 1), [59] where the slope (b) is 1.0 for capacitive materials and 0.5 for battery-type materials. Although a clear-cut boundary is not easy to define, materials such as conductive polymers, having a "transition" area between capacitive and battery-type behaviors, are defined as pseudocapacitive hybrid energy-storage systems, falling into the range of 0.5-…”
Section: Electrochemical Performancementioning
confidence: 99%
“…The capacitance values of the polymers from their CV ( C CV ) measurements, were calculated using the Equation () 40,41 : CCV=I.dVΔV.A.υ where I is the current, V is the potential window, A is the electrode area, and υ is the scan rate. The results suggested that P(D1‐1E) showed the best capacitive behavior among the polymers (Figures 3B and S3).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, P(D1-1E) displayed the highest charge density, obtained from CV. The capacitance values of the polymers from their CV (C CV ) measurements, were calculated using the Equation (1) 40,41 :…”
Section: Electrochemical Properties Of Polymer Filmsmentioning
confidence: 99%
“…Compared to EDLC where carbon-based materials [2] are frequently adopted, pseudocapacitors and battery-type capacitors usually employ redox active species, including metal oxides [3,4] and conducting polymers as electrode material and generally show larger capacitances [5]. Among them, conducting polymers feature flexibility and easily-tailored redox properties by functionalization [6], and are utilized as electrode materials to effectively tune the achievable voltage of supercapacitors [7,8].…”
Section: Introductionmentioning
confidence: 99%